Problematika problematika guru dalam masa transisi Kurikulum 2013 ke Kurikulum Merdeka pada jenjang SD di SDN Telok kecamatan Katingan Tengah kabupaten katingan: problematika guru dalam masa transisi Kurikulum 2013 ke Kurikulum Merdeka pada jenjang SD di SDN Telok kecamatan Katingan Tengah kabupaten katingan - yunistira, elin; Kristiani Natalina, Ph.D, Kristiani Natalina, Ph.D; Laila Rahmawati, S.Pd,. M.Pd, Laila Rahmawati, S.Pd,.M.Pd (Sangkalemo : The Elementary School Teacher Education Journal, 2024)
The purpose of this article is to determine the teacher problematics in the transition period of Kurikulum 2013 to Kurikulum Merdeka at primary school level at SDN Telok, Katingan Tengah, katingan. The method of this research is by conducting data using an observation and an interview. The result showed in this research is there were two main findings, namely the teacher’s first problem is they were having a difficulty in adapting to the new method of teaching from the traditional method. The second problem is they were having a difficulty in adapting with the technology and the applications that are used in Kurikulum Merdeka. In conclusion, the teacher’s main problem is in adapting to new method and adapting in using technology